Digitally-Driven Architecture - Henriette Bier; Terry Knight (Footprint)
The shift from mechanical to digital forces architects to reposition themselves: Architects generate digital information, which can be used not only in designing and fabricating building components but also in embedding behaviours into buildings. This implies that, similar to the way that industrial design and fabrication with its concepts of standardisation and serial production influenced modernist architecture, digital design and fabrication influences contemporary architecture. While standardisation focused on processes of rationalisation of form, mass-customisation as a new paradigm that replaces mass-production, addresses non-standard, complex, and flexible designs. Furthermore, knowledge about the designed object can be encoded in digital data pertaining not just to the geometry of a design but also to its physical or other behaviours within an environment. Digitally-driven architecture implies, therefore, not only digitally-designed and fabricated architecture, it also implies architecture – built form – that can be controlled, actuated, and animated by digital means.